A Study of Extended Spectrum Β-Lactamase (ESBL) And AMPC Β-Lactamase Producing Klebsiella Pneumoniae in Neonatal Intensive Care Unit at Tertiary Care Hospital, Ahmedabad - Dhara J Modi; Bhaumik V Patel; Mitesh H Patel; Seema S Bhatt; Nidhi K Sood; Mahendra M Vegad (Medsci Publications, 2012)
Background & objectives: Clinical laboratories need to develop quick screening methods for detection of Extended Spectrum β-Lactamases (ESBL) & Amplified C (AmpC) β-Lactamase, so that the appropriate medication can be started without delay. Here, we reported the screening & confirmatory methods for detection of ESBL & AmpC in Klebsiella pneumoniae in Neonatal Intensive Care Unit (NICU). Methods: We had tested 600 blood culture samples from the NICU patients. From the positive bacterial isolates, Klebsiella pneumoniae were screened for ESBL & AmpC production followed by confirmatory methods as per Clinical Laboratory Standard Institute (CLSI) guidelines. Results: Out of the 600 blood culture, 266 were positive for microbial growth. Among them, Klebsiella pneumoniae were in 54 patients. Out of 54 Klebsiella pneumoniae, 48 were positive for ESBL in screening method. Out of 48, 41 isolates were ESBL positive & 4 were AmpC positive by Confirmatory test (Modified Three Dimensional Method for AmpC). Interpretation & conclusions: The prevalence of ESBL & AmpC producing Klebsiella pneumoniae in NICU at our institute is 75.92% & 7.4% which is very alarming, and it requires strict implementation of infection control guidelines in NICU by safe hygiene practices, restricted use of broad spectrum antibiotics as empirical therapy in septicemic cases and also formulation of uniform antibiotic policy for such patients based on the current trend of antibiotic resistance. This can be helpful in preventing emergence of multidrug resistance in such organisms.